2017
DOI: 10.15296/ijwhr.2018.39
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Female Adolescents’ Reproductive Health Needs: A Systematic Review

Abstract: Introduction Adolescence is a transitional stage of psychological and physical development that brings change, growth, and, all too often, health risks to reproduction (1). It is considered by the World Health Organization (WHO) as the period between 10 and 19 years of age (2). The need for quality improvement in health services intended for adolescents, including health care services related to human reproduction, has been recognized around the world (3). It was reported that sexual violence, pregnancy, sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…There has been a developing comprehension that SSE is affected by macro factors that are substantial for realization of decision-making about sexual issues and behavior (11). SSE (i.e.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a developing comprehension that SSE is affected by macro factors that are substantial for realization of decision-making about sexual issues and behavior (11). SSE (i.e.…”
Section: Contextmentioning
confidence: 99%
“…Although evidence suggests that SSE is necessary for the sexual function and safe sexual behavior (11), the factors related to the SSE remain marginalized and neglected in sexual health education programs. While understanding these factors may improve people's knowledge, attitudes, beliefs or behavioral practices and could lead to a reduction in risky sexual behavior (12).…”
Section: Contextmentioning
confidence: 99%
“…There are no explicit policies supporting the provision of RH education for them in Iranian schools. For the successful implementation of the school-based component of this intervention, participatory teaching methods that engage students are necessary ( Panjalipour et al ., 2018 ). Also, the healthcare system in Iran does not provide RH services tailored for adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The current study revealed that participants do not have enough, or correct knowledge about RH. This problem was reported in several Iranian studies ( Simbar et al ., 2017 ; Mirzaii Najmabadi et al ., 2018 ; Panjalipour et al ., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mothers, who have an elevated attachment to their infants are often aware of their needs, and this feeling affects many aspects of the infant's personality, such as their sense of curiosity, and ability to socialize and trust (7). In this relationship, the infant would learn the manner of relating to and communicating with others, and therefore, it is considered as the foundation for the formation of the child's future behaviors (8).…”
Section: Introductionmentioning
confidence: 99%